Characteristics of LGV repeaters: analysis of LGV surveillance data. (15th January 2014) - Rönn, Minttu; Hughes, Gwenda; White, Peter; Simms, Ian; Ison, Catherine; Ward, Helen
Abstract : Objectives: A number of individuals have acquired lymphogranuloma venereum (LGV) infection multiple times since its re-emergence. We describe the characteristics of reinfections and those who acquire them. Methods: The LGV Enhanced Surveillance system collected detailed information on LGV episodes in the UK from 2004 to 2010. Using logistic regression we compared the baseline characteristics of men who have sex with men (MSM) who had a repeat LGV episode ('repeaters') to MSM with a single reported episode ('non-repeaters'). Results: There were 66 individuals among the 1281 MSM (5.2%) with LGV episode who had a recorded reinfection during the data collection period. Those who acquired LGV reinfection were more likely to be HIV positive (97% vs 79%), visit a clinic in London (OR 2.0, 95% CI 1.1 to 3.8), and have hepatitis C (OR 2.2, 95% CI 1.1 to 4.6) or concurrent gonorrhoea (OR 2.2, 95% CI 1.2 to 3.8) on their first recorded LGV episode. Repeaters reported higher levels of unprotected sex, but behavioural variables were not significantly different between repeaters and non-repeaters. Conclusions: Among LGV repeaters, risk behaviour alone did not explain subsequent reinfection. LGV repeaters have a high level of other sexually transmitted infections (STIs) which may be linked to their central position in the sexual network that contributes to their heightened risk of STI acquisition. Given the low prevalence of LGV in the general MSM population, momentary increases in incidence in subsets of the population may be an important factor for LGV risk where the overall level of sexual risk behaviour is higher. Validating this would require research into sexual network structures.